Player piano - Vonnegut, Kurt. (New York, NY : Charles Scribner's sons, 1952)
Engineer Paul Proteus must find a way to live in a world dominated by a supercomputer and run completely by machines.
First published in 1952.
Keywords: Engineers -- Fiction; Computers -- Fiction; Utopian fiction; Science fiction